The role of ants, especially the fire ant, Solenopsis geminata (Hymenoptera: Formicidae), in the biological control of tropical upland rice pests - Way, M.J.; Javier, G.; Heong, K.L. (Cambridge University Press, 2002)
Predatory ants are omnipresent year-round in upland (dryland) rice fields in the Philippines. At least 14 species were identified of which the very aggressive Solenopsis geminata (Fabricius) and also Tapinoma sp. nr indicum Forel usually predominated. Some highly aggressive species, notably Pheidolegeton spp. and Bothriomyrmex dalyi Forel were localized. Solenopsis geminata flourished within many fields, not only during the crop season but also throughout dry season fallows where they remained aggressively predatory. Rice plants infested with brown planthopper Nilaparvata lugens (Stål) were usually found within a few hours and S. geminata workers were quickly recruited to N. lugens aggregates. Predation was usually incomplete and workers began to solicit the few remaining late instar or adult N. lugens survivors. These oviposited but no second generation nymphs appeared. There was a surge of recruited ants at the time of N. lugens egg hatch when surviving adults were also killed. Initially, S. geminata alone killed N. lugens aggregates less quickly than with the whole predator complex but ultimately its sole effect was as great as that of the complex. Scattered N. lugens adults, corresponding to numbers that initially colonize rice plants, were eliminated as quickly by S. geminata alone as by the predator complex. Tapinoma indicum occurring separately or with S. geminata on the same plant contributed to predation of N. lugens especially on young nymphs. Solenopsis geminata attacked other insects on rice notably leaffolders of which 97% mortality was recorded when they were exposed throughout egg and larval stages. The role of S. geminata as a predator of upland rice pests is discussed in the context of known biological control of pests of non-rice dryland crops in the tropics and sub-tropics by S. geminata and other Solenopsis spp.